Fostering Work Engagement through the Quality of Social Exchange: The Mediating Role of Job Satisfaction - Rahadhian, Liko Noor Rafianto; Rahmawati, Rini; Claudia, Meiske; Rifani, Ahmad (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of Leader–Member Exchange (LMX) and Team–Member Exchange (TMX) on work engagement with job satisfaction serving as a mediating variable. Using a quantitative approach, data were collected from 182 employees of a regional water supply company in Banjarmasin and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The analysis demonstrates that both LMX and TMX have significant positive effects on employees’ job satisfaction and work engagement. Furthermore, job satisfaction serves as a bridge linking social exchange quality (LMX and TMX) and work engagement. Collectively, these insights highlight the importance of supportive and trusting relationships in enhancing employees’ satisfaction and engagement within their organizations.